SLIMs: Smart Lightweight Indoor Maps - Sathittham Sangthong; Boonchana Purahong; Attasit Laskul (My University, 2013)
This paper presents a smart lightweight indoor navigation system called "SLIMs".The system divided into 3 main parts, 1) Indoor Positioning system 2) Indoor Navigation system 3) Administration Management system.SLIMs system takes advantage of the development of short length communication technology or Near Field Communication (NFC) combined with Quick Respond Code (QR Code) with have a very low cost.According to these technologies, it can help to identifying the exact location of the user and facilitated by scanning the tag that is placed all over the building.This system also combined with independent navigation system based on Inertial Navigation System (INS) or Dead Reckoning (DR) method, to give an instruction to the user to reach the destination more accurately.This system also comes with the management of the administrator who can work online.All of this will help in terms of saving cost the devices, less complicated installation, low cost of system maintenance and energy savings as well.
Keywords: Indoor and Outdoor Localization Technologies